Genealogy of the Omsk Batyushkins family in first half of the 19th century according to church records - D. I. Petin (Омский научный вестник: Серия "Общество. История. Современность")
The work based on unpublished sources (church records), presents an analytical review of information about the representatives of the Batyushkins family — close direct ancestors of the subsequently wealthy and famous family in prerevolutionary Omsk. The purpose of the work is to identify the genealogical origins and connections of the Batyushkins family, which contributed to the entry of this family into the merchant class. The methodological basis of the study is a combination of the anthropological approach and the historical-genetic method. In conclusion, the special role of the merchant E. A. Terekhov in acquiring a new status for the Batyushkins family and in the general consolidation of the Omsk business families at the personal communicative level in the second half of the 19th century is emphasized.